Long noncoding RNA HAGLR sponges miR‐338‐3p to promote 5‐Fu resistance in gastric cancer through targeting the LDHA‐glycolysis pathway. (5th December 2021) - Hu, Jing; Huang, Lujie; Ding, Qi; Lv, Jiaming; Chen, Zhe
Abstract: Gastric cancer (GC) is one of the most common human malignancies due to its invasiveness and metastasis. 5‐Fu is a widely applied chemotherapeutic agent against GC. Although 5‐Fu therapy has achieved improvements in GC treatment, a large fraction of patients developed drug resistance which significantly limited its clinical applications. Recent studies revealed the pivotal roles of long noncoding RNAs (lncRNAs) in tumorigenesis and progressions of various tumors, including GC. However, the biological roles and molecular mechanisms of lncRNA HAGLR in GC remain unclear. Here, we report HAGLR was upregulated in both GC tissues and cell lines. In addition, HAGLR was associated with a poorly survival rate of GC patients. Blocking HAGLR inhibited GC cells proliferation and sensitized GC cells to 5‐Fu. Bioinformatical analysis and luciferase assay demonstrated that HAGLR sponged microRNA (miR)‐338‐3p, which functions as a tumor suppressor in GC to downregulate its expressions. Moreover, from the established 5‐Fu resistant GC cell line (HGC27 5‐Fu R), we detected significantly elevated HAGLR, downregulated miR‐338‐3p, and glucose metabolism compared with parental HGC27 cells. We identified lactate dehydrogenase‐A (LDHA), a glucose metabolism key enzyme, was the direct target of miR‐338‐3p in GC cells. Rescue experiments demonstrated that restoration of miR‐338‐3p in HAGLR‐overexpressing HGC27 5‐Fu R cells successfully overrode the HAGLR‐promoted 5‐Fu resistance through targeting LDHA. Taken together, this study revealed essential roles and molecular mechanisms for the HAGLR‐mediated 5‐Fu resistance in GC, contributing to the development of new noncoding RNA‐based therapeutic strategies against chemoresistant GC.